2012
DOI: 10.1096/fj.12-222695
|View full text |Cite
|
Sign up to set email alerts
|

Th2 differentiation is necessary for soft tissue fibrosis and lymphatic dysfunction resulting from lymphedema

Abstract: Lymphedema is a dreaded complication of cancer treatment. However, despite the fact that >5 million Americans are affected by this disorder, the development of effective treatments is limited by the fact that the pathology of lymphedema remains unknown. The purpose of these studies was to determine the role of inflammatory responses in lymphedema pathology. Using mouse models of lymphedema, as well as clinical lymphedema specimens, we show that lymphatic stasis results in a CD4 T-cell inflammation and T-helper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
296
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 188 publications
(325 citation statements)
references
References 36 publications
24
296
2
3
Order By: Relevance
“…Using a surgical mouse model of axillary lymphadenectomy in which the draining lymph nodes of the forelimb are removed, our group has shown that even this relatively minor injury increases the expression of adipose differentiation genes such as CEPB-␣ and Ppar-␥ (2) as well as early inflammatory cascades in the forelimb subcutaneous tissues (39). By comparing tissues harvested from mice that had undergone axillary lymph node dissection with a more severe model of lymphatic injury in the mouse tail, we have also shown that the degree of adipose deposition is related to the severity of lymphatic obstruction and tissue inflammation (6). The association between inflammation and adipose deposition is important and supported by our previous studies demonstrating that depletion of T cells or blockade of T-helper type 2 (Th2) cell inflammation potently inhibits adipose tissue deposition in the mouse-tail model (6,40).…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…Using a surgical mouse model of axillary lymphadenectomy in which the draining lymph nodes of the forelimb are removed, our group has shown that even this relatively minor injury increases the expression of adipose differentiation genes such as CEPB-␣ and Ppar-␥ (2) as well as early inflammatory cascades in the forelimb subcutaneous tissues (39). By comparing tissues harvested from mice that had undergone axillary lymph node dissection with a more severe model of lymphatic injury in the mouse tail, we have also shown that the degree of adipose deposition is related to the severity of lymphatic obstruction and tissue inflammation (6). The association between inflammation and adipose deposition is important and supported by our previous studies demonstrating that depletion of T cells or blockade of T-helper type 2 (Th2) cell inflammation potently inhibits adipose tissue deposition in the mouse-tail model (6,40).…”
mentioning
confidence: 76%
“…Control animals are treated with an axillary skin incision without lymph node excision. To study the effects of more significant lymphatic injury and adipose deposition, we used a well-described mouse tail model of lymphedema (3,4,6,40). In this model, the superficial and deep lymphatic system of the midportion of the tail are disrupted by excising a 2-mm portion of the skin and microsurgically ligating the deep lymphatic channels that run along the lateral tail veins.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations